Neutral current neutrino-94Mo scattering in the context of the QRPA method - Balasi, K. G.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
A systematic investigation of neutrino-nucleus reaction rates at low and intermediate energies of the stable 94Mo isotope is performed. Differential and integrated cross sections for neutrino inelastic scattering off the aforementioned target are calculated for neutrino energies εi ≼ 100 MeV. The nuclear wave functions for the initial and final nuclear states are constructed in the context of the quasi-particle random phase approximation (QRPA). The reliability of our method is tested by checking the reproducibility of the low-lying energy spectrum of the isotope under investigation.